2022
DOI: 10.1161/jaha.121.024903
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Implications of Prestent Pullback Pressure Gradient and Poststent Quantitative Flow Ratio in Patients Undergoing Percutaneous Coronary Intervention

Abstract: Background Coronary diffuse disease associates with poor outcomes, but little is known about its role after percutaneous coronary intervention (PCI). We aimed to investigate the prognostic implication of pre‐PCI focal or diffuse disease patterns combined with post‐PCI quantitative flow ratio (QFR). Methods and Results Pre‐PCI QFR derived pullback pressure gradient (PPG) (QFR‐PPG) was measured to assess physiological disease patterns for 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 23 publications
3
11
0
Order By: Relevance
“…Angio‐FFR permits not only the measurement at the distal part of the vessel, but also the virtual pullback of the entire vessel. Feasibility of angio‐FFR based pullback quantification in assessing physiological distribution and local severity of coronary atherosclerosis has been confirmed in previous studies 11,12,19 . In the present analysis, with the angio‐FFR from another vendor, pullback pressure gradient was also quantified successfully in all included vessels.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Angio‐FFR permits not only the measurement at the distal part of the vessel, but also the virtual pullback of the entire vessel. Feasibility of angio‐FFR based pullback quantification in assessing physiological distribution and local severity of coronary atherosclerosis has been confirmed in previous studies 11,12,19 . In the present analysis, with the angio‐FFR from another vendor, pullback pressure gradient was also quantified successfully in all included vessels.…”
Section: Discussionsupporting
confidence: 77%
“…Feasibility of angio-FFR based pullback quantification in assessing physiological distribution and local severity of coronary atherosclerosis has been confirmed in previous studies. 11,12,19 In the present analysis, with the angio-FFR from another vendor, pullback pressure gradient was also quantified successfully in all included vessels. In the prospective iFR GRADIENT Registry, 20 the authors revealed that iFR pullback predicted the physiological outcome of PCI with a high degree of accuracy.…”
Section: Rationale For Angio-ffr Based Physiological Map Before Pcimentioning
confidence: 97%
“…This difference could be attributed firstly to the inclusion of neutral FFR studies in the meta-analysis by Griffioen et al [ 38 ]. Secondly, in contrast to Griffioen et al we included two large QFR studies that reported significantly higher risks of adverse cardiovascular events in patients with lower post-PCI QFR values [ 18 , 19 ]. Accordingly, a recent meta-analysis of post-PCI invasive FFR studies reported similar results, supporting the prognostic value of post-PCI physiology [ 39 , 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…The immediate post-stenting measurement of the FFR could aid in optimizing revascularization results and potentially improve outcomes as it is well established that suboptimal PCI is an independent predictor of major cardiac adverse events [ 13 , 14 , 15 ]. Recent studies demonstrated the role of the post-PCI angiography-derived FFR as a predictor of a vessel- or patient-oriented outcomes in patients with stable CAD, acute coronary syndromes, or in-stent restenosis [ 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 ]. The primary objective of this meta-analysis was to evaluate whether the post-PCI angiography-derived FFR predicts coronary adverse events in CAD patients undergoing PCI.…”
Section: Introductionmentioning
confidence: 99%
“…The point-by-point functional distribution provided by the virtual computational pressure pullback along the vessel length can inform the functional pattern of coronary artery disease either qualitatively (eg, step-ups, progressive decline, or mixed) or quantitatively and further guide and optimize PCI ( Supplemental Figure 2 ). 145 , 146 , 147 …”
Section: Wire-free Image-based Physiologic Assessmentmentioning
confidence: 99%